PENERAPAN TEKNOLOGI MESIN PENCETAK BAKSO BERBASIS PNEUMATIK PADA UMKM - Suwandi, Dedi; Sifa, Agus; Supriatun, Evi (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
Meatballs are one of the favorite foods of Indonesian people. The naming of meatballs depends on the place where they are made, the meat used, the way they are served, the way they are made, and their size and shape so the names vary greatly. Meatballs are generally round with an average diameter of 15-35 mm. So far, the process of making meatballs in the community still uses manual methods, by forming the meatball dough using hands and a spoon. Hold the dough in your hands and then knead it so that it comes out between the holes of your index finger and thumb. The dough that comes out is round, then scooped out using a spoon and put into a container filled with hot water. This manual meatball molding process requires skill, and patience and has the danger of being exposed to hot water so not everyone can do it. With this opportunity, a meatball-making machine with a pneumatic system was created. This machine uses a power source from a compressor of at least 10 bar which drives two pneumatic systems. The first pneumatic system moves the TBC 40-400 pneumatic cylinder piston which presses the dough down into the mold. The second pneumatic system drives two 25X300 pneumatic cylinder pistons. The combination of the two pneumatic systems is capable of producing 60 meatballs per minute with a diameter of 30 mm.